2006
DOI: 10.1523/jneurosci.5507-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Sprouting Drives Hippocampal Cholinergic Reinnervation That Prevents Loss of a Muscarinic Receptor-Dependent Long-Term Depression at CA3–CA1 Synapses

Abstract: Degeneration of septohippocampal cholinergic neurons results in memory deficits attributable to loss of cholinergic modulation of hippocampal synaptic circuits. A remarkable consequence of cholinergic degeneration is the sprouting of noradrenergic sympathetic fibers from the superior cervical ganglia into hippocampus. The functional impact of sympathetic ingrowth on synaptic physiology has never been investigated. Here, we report that, at CA3-CA1 synapses, a Hebbian form of long-term depression (LTD) induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
90
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 92 publications
11
90
2
Order By: Relevance
“…Additionally, we have shown that mLTD requires activation of M 1 mAChRs; it can be induced using the selective M 1 receptor agonist McN-A-343 (50 M) and prevented by the selective M 1 toxin MTx-7 (100 nM) (Scheiderer et al, 2006). Note the larger transient depression occurring during CCh application compared with during application of Methox.…”
Section: Mltd and Ne Ltd Are Independent Plasticitiesmentioning
confidence: 90%
See 4 more Smart Citations
“…Additionally, we have shown that mLTD requires activation of M 1 mAChRs; it can be induced using the selective M 1 receptor agonist McN-A-343 (50 M) and prevented by the selective M 1 toxin MTx-7 (100 nM) (Scheiderer et al, 2006). Note the larger transient depression occurring during CCh application compared with during application of Methox.…”
Section: Mltd and Ne Ltd Are Independent Plasticitiesmentioning
confidence: 90%
“…Baseline transmission was acquired using 0.2 Hz (100 s duration) stimulation frequency and the stimulus intensity was adjusted to generate a fEPSP of 0.8 -1.0 mV in amplitude. After acquisition of a stable baseline of transmission (at least 20 min), agonists were bath applied to induce LTD. mLTD was induced via a 10 min application of carbachol (CCh) (50 M) or the selective M 1 agonist [4-(m-chlorophenylcarbamoyloxy)-2-butynyltrimethylammonium] (McN-A-343) (50 M) (adapted from Kirkwood et al, 1999; see also Scheiderer et al, 2006) and NE LTD was induced by a 10 min bath application of the ␣1 agonist methoxamine (Methox; 40 M) (Scheiderer et al, 2004(Scheiderer et al, , 2006. Receptor antagonists and inhibitors of the signaling molecules were bath applied at least 10 min before application of agonists to induce LTD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations